Effect of Carboxyl Methyl Cellulose Addition and Heating Time on The Production of Keribang Barbant Jam (Dioscorea alata L.) - Nuraini, Michelle Nattaya Narerat; Purwayantie, Sulvi; Hartanti, Lucky; Saputri, Nur Endah (Media Publikasi Cendekia Indonesia, 2023)
Keribang tubers are a prospective local food and can be used as food for claims and food diversification. Anthocyanins from keribang tubers can be processed into food products, one of them is made into jam. Jam is a food product with a gel consistency, therefore a thickening agent such as Carboxyl Methyl Cellulose (CMC) is needed. The purpose of this study was to determine the effect of adding CMC and heating time as well as the best combination to the physicochemical characteristics of keribang tuber jam. This research design used a Randomized Block Design (RAK) with two treatment factors, consisting of 3 treatments of CMC (0.5%; 0.75%; and 1%) and 2 treatments of heating time (15 minutes and 20 minutes), with 4 replications. Parameters observed were water content, total polyphenols, total dissolved solids, antioxidant activity, smearing power, and organoleptic tests. The best treatment was tested using the effectiveness index test. The results showed that CMC concentration treatment and heating time did not significantly affect the water content, total dissolved solids content, antioxidant activity, and spread ability, but significant on the total polyphenol content value in keribang tubers jam. The organoleptic test showed that the panelists preferred the keribang tubers jam with a CMC concentration of 0.5% and a heating time of 15 minutes in terms of color and texture. Based on the effectiveness index test, the best treatment for keribang tubers jam was 1% CMC concentration and 20 minutes of heating time